The Crisis $1 (BVolume 07s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Crisis $1 (BVolume 07" by Winston Churchill is a historical novel published in 1901. Set in St. Louis during the years before the Civil War, it follows Stephen Brice, a young lawyer with Union sympathies, as he becomes entangled with a Southern family in a deeply divided Missouri. Romantic rivalries emerge between four characters while Abraham Lincoln's opposition to slavery's expansion transforms lives and loyalties. The novel dramatically depicts the Western theater of war, portraying how personal conflicts mirror the nation's struggle toward reconciliation. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Crisis_(novel)
Release date is 2004-10-19
Produced by David Widger
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction